The Baladang System Is Environmental Education Based on Local Wisdom - Yuliantoro Yuliantoro; Dewi Liesnoor Setyowati; Thriwaty Arsal; Apik Budi Santoso (International Conference on Science, Education, and Technology, 2023)
It is undeniable that the challenges of the development of science and technology in agriculture also have a negative effect on humans. Agricultural problems in farming systems instead of increasing agricultural production, people tend to use chemical pesticides, which affect environmental damage and decrease soil quality and even disrupt human health. This study uses a descriptive qualitative approach to answer the research objectives; The problem of environmental damage due to the community's farming system, and the value of baladang local wisdom in maintaining soil fertility in agricultural patterns. Description of research results; 1). Problems in the pattern and system of rice farming in the Kuantan Singingi community, the majority of people use pesticides, so that the level of soil fertility is maintained, it is necessary to have rules approved by members of the national adat community. The effects of the use of pesticides disrupt soil fertility, the environment is polluted when pesticides are used in large quantities even for a long period of time, and the level of human health, especially farmers, when spraying rice plants is even harmful to the health of all living things. 2). Baladang's local artistic value is a pattern of community agriculture that seeks to balance the natural environment with humans by stopping for a moment in cultivating rice with interludes of buffalo grazing in the fields when the rice harvest is finished. This tradition has long been agreed upon in the agricultural system of the national society. The process of raising buffalo is also in groups so that when the buffalo are released together there are indeed a lot of buffalo so that the buffalo dung and urine are also one of the media to enrich the soil again after the harvest season is over. The traditions of this community are also maintained and preserved in the midst of today's developments. This is in line with the fact that the environmental problems faced by humans are actually human life itself, namely a life that is full of simplicity and actions that do not prioritize greed, so that nature will be protected by humans. The real behavior carried out by the community is local wisdom as a view of life in protecting the environment. The view of life that has been carried out by the community if carried out widely will become environmental education for the entire wider community.